25 years of the AMTREAT® process treating high‐strength ammonia liquors. (30th July 2020) - Bungay, Steve
Abstract: Over the last 30 years, a number of biological treatment processes have emerged for treating high‐strength ammonia liquors arising from the dewatering of anaerobic digestate. The AMTREAT® process was the first process to become established and recognised as a viable and reliable process to treat these high‐strength ammonia liquors. The process is a high‐rate activated sludge plant supplied by ACWA Services Ltd. The first full‐scale plant was installed in 1995, treating centrate produced when dewatering anaerobically digested sludge. The process is a compact, high‐rate ammonia treatment system, which has a relatively small footprint compared to conventional activated sludge treatment processes. Originally designed to fully nitrify dewatering ammonia liquors by controlling the environmental conditions of the treatment reactor, the process has evolved first to include alkalinity recovery and subsequently to offer total nitrogen removal. This paper discusses the development of the AMTREAT® process from its initial development in 1992, to the modern day third generation plants which achieve typical achieve ammonia removal exceeding 99% and total nitrogen removal in excess of 80%.